Edukasi Budidaya Galo-galo untuk Peningkatan Produktivitas Masyarakat di Kelurahan Alai Gelombang Kota Pariaman - Ediset Ediset; Amrizal Anas; Rusdimansyah Rusdimansyah; Simel Sowmen; Amna Suresti; Rahmi Wati; Syofyan Syofyan (Warta Pengabdian Andalas, 2023)
A simple cultivation process and an excellent opportunity to improve the household economy is a type of business that must be continuously educated in the community. Galo-galo (Trigona bees) are a group of small, stingless bees belonging to the Meliponini group, which are closely related to the stinging honey bees (Apis spp) in the Apidae tribe, which can be cultivated. Galo-galo cultivation is a simple type of business and has good economic prospects for the community; for this reason, community service activities need to be carried out in Alai Galombang Village Pariaman City, West Sumatera, namely a sub-district that has potential natural resources that can be used to provide nectar (food source), provide pollen (seed producer) and provide resin (nest builder) as well as guarantee water availability. Galo-galo education in the community uses counselling (socialization) and mentoring methods. The results of the activity show that education on Galo-galo cultivation among the community has resulted in fundamental changes in interest, knowledge and skills in Galo-galo cultivation. The proof is that the community already has four colonies and has carried out the first harvest in two colonies with a production output of 450 grams, potentially improving its economy.